Post-critical behavior of an auto-parametric aero-elastic system with two degrees of freedom. (May 2020) - Náprstek, J.; Fischer, C.
Abstract: A generalized two-degree-of-freedom non-linear mathematical system with non-linear gyroscopic and non-conservative terms was used to set up a model for heave and pitch self-excited motion. The stability conditions for a girder with a bluff cross-section in wind flow were identified and presented. The analysis, based on the Routh–Hurwitz conditions and a numerical evaluation of the model, comprises both the self-excited case and an assumption of a harmonic load. The boundaries between different response types that depend on the frequencies of two principal aero-elastic modes are shown. The properties of the response located at these limits and the tendencies of the response in their neighborhood are discussed. The results can be used to explain several experimentally observed effects. Highlights: Stability conditions for a girder in wind flow are identified and presented. The non-linear 2DOF model is based on the generalized van der Pol equation. The analysis comprises both the self-excited and harmonic external load.